Event‐triggered output feedback H∞ control for networked control systems. (17th October 2018) - Shen, Yanjun; Li, Fengjiao; Zhang, Daoyuan; Wang, Yan‐Wu; Liu, Yungang
Summary: This paper investigates event‐triggered output feedback H ∞ control for a networked control system. Transmitted through a network under an event‐triggered scheme, the sample outputs of the plant are used to drive the dynamical output feedback controller to generate a new control signal in the discrete‐time domain. The discrete‐time control signals are also transmitted through the network to drive the plant. As a result of two types of transmission delays, the controlled plant and the dynamical output feedback controller are driven by the discrete‐time outputs and control signals at different instants of time. An interval decomposition method is introduced to place the controlled plant and the output feedback controller into the same updated time interval but with updated signals at different instants. Based on a proper Lyapunov‐Krasovskii functional, sufficient conditions are derived to ensure H ∞ performance for the controlled plant. Finally, numerical simulations are used to demonstrate the practical utility of the proposed method.